Crescentic Glomerulonephritis and Membranous Nephropathy: A Rare Overlap - Mohamedanwar Ghandour; Heba Osman; Samer Alkassis; Alix Charles; Kristina Zalewski; Jarrett Weinberger; Yahya Malik-Osman; Zeenat Y. Bhat (Case Reports in Nephrology)
Background. Membranous nephropathy (MN) is a disease that affects the basement membrane of the glomeruli of the kidney resulting in proteinuria. The concurrent incidence of vasculitic glomerulonephritis and MN in the same patient is unusual. Herein, we report a case with this unusual combination. Case. Our patient is a 53-year-old Hispanic male with a medical history of tobacco use, type 2 diabetes mellitus, and hypertension who presented with hematuria and was found to have nephrotic range proteinuria and renal impairment. Blood workup revealed positive ANCA serology, which led to a renal biopsy that showed crescentic vasculitis in addition to membranous nephropathy. The patient was started on intermittent hemodialysis (HD) and treated initially with intravenous (IV) pulse steroids; subsequently, oral prednisolone and IV cyclophosphamide were initiated. The patient remained HD dependent at the time of discharge with the resolution of hematuria. A follow-up with an outpatient nephrology clinic was arranged. Conclusion. Membranous nephropathy complicated by crescentic glomerulonephritis has a more aggressive clinical course and decline in renal function compared to MN alone which can lead to initiating renal replacement therapy. However, immunosuppressive drugs can result in significant improvement of renal function if started early enough.